Putting the farmer first - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
'Farmer First: farmer innovation and agricultural research' 240pp, 1989, price UKL 12.95 hardback ISBN 185339 008 9 UKL 2.25 paperback ISBN 1 85339 007 8